PELAKSANAAN KEWENANGAN PROGRAM REHABILITASI HUTAN: (STUDI PADA UNIT PELAKSANA TEKNIS KESATUAN PENGELOLAAN HUTAN SINGINGI DI KABUPATEN KUANTAN SINGINGI TAHUN 2017) - Nisa, Novi Khoirun; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Forest as national development capital have real benefits for life. Forest’s problem certainly involve forest destruction. Therefore there is need for rehabilitation efforts. This study wanted to see how forest rehabilitation was carried out according to the authority of each level of government. The research objective is to see how the implementation of forest rehabilitation is based on the authority of the central and regional governments and at the regency/city level through the Singingi Forest Management Unit Technical Implementation Unit. The theory used Developmental State theory which describes the state still plays a strong role in the era of regional autonomy. The type of research in this case is a type of descriptive research with qualitative analysis methods. Research location in Singingi Forest Management Unit Technical Implementation Unit Technique with collecting interview data and documentation. While data analysis is by qualitative analysis. The data uses triangulation as a technique to check the validity of data. As one of the concurrent government affairs in the forestry sector, the implementation of forest rehabilitation is divided between the government and the regional government. This can be seen in Law Number 23 of 2014 concerning Regional Government which sees that the state still plays a major role in regulating forest rehabilitation policies from planning to implementation through the Central Government units located in the area, namely the Management of Watersheds. This unit has authority in planning the preparation and stipulation of plans for rehabilitation of forest and land watersheds / sub-watersheds, implementation and supervision of forest rehabilitation. Whereas Local Governments have authority in planning and implementing forest rehabilitation at the level of Forest Management Units (KPH). The Central Government also conducts a forest rehabilitation program through its unit in Kuantan Singingi District which already has a Forest Management Unit Technical Implementation Unit as a unit of the Provincial Environmental and Forestry Service. So that it can be seen that the role of the Central Government is still large in forest rehabilitation programs at the district / city level in the era of regional autonomy. Keysword: The Role of The State, Governments Authority, and Forest     Rehabilitation